Translation of Power and Solidarity Pronouns in Qur’anic Rhetoric - Amirdabbaghian, Amin (Faculty of Persian Literature and Foreign Languages, Islamic Azad University, South Tehran Branch, 2017)
Translation of the Holy Quran can be difficult for translators in terms of accuracy and translatability. Sometimes translators fail to render the Quranic thoughts because of the lack of language features in target languages. This results in an unfavorable interpretation. One of the challenging aspects of translating Quran is reference switching as rhetorical devices, which are widespread in the book due to the aesthetic aspects of the Arabic language. Rendering rhetorical devices may lead to misinterpreting the Quran as the target languages might not have the same context as Arabic. The ongoing research discovers several rhetorical problems in the English translation of the Quran by Abdel - Haleem in terms of power and solidarity relations on the basis of Brown and Gilman personal pronoun description. This study provided a brief introduction and review about “tenor” – interpersonal relationship among the text – that is a part of Hallidayan functional linguistics, which was the framework for data analysis in this study and the pronouns of power and solidarity as rhetorical devices. This study also investigated the analysis of the six selected and randomly chosen samples and their English translations regarding reference switching as a rhetorical device in the tenor of the target texts. The results of the study revealed that the translator was not successful in switching the references amongst the pronouns in English translation and the tenor in target text was also different from the source one.